2011
DOI: 10.1007/s10803-011-1418-3
|View full text |Cite|
|
Sign up to set email alerts
|

Melatonin for Sleep in Children with Autism: A Controlled Trial Examining Dose, Tolerability, and Outcomes

Abstract: Supplemental melatonin has shown promise in treating sleep onset insomnia in children with autism spectrum disorders (ASD). Twenty-four children, free of psychotropic medications, completed an open-label dose-escalation study to assess dose-response, tolerability, safety, feasibility of collecting actigraphy data, and ability of outcome measures to detect change during a 14-week intervention. Supplemental melatonin improved sleep latency, as measured by actigraphy, in most children at 1 or 3 mg dosages. It was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
213
0
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(226 citation statements)
references
References 31 publications
10
213
0
3
Order By: Relevance
“…A growing body of evidence indicates abnormal melatonin secretion and circadian rhythmicity in children with neurodevelopmental disorders, specifically ASD, which may explain the abnormal development of sleep/wake cycles, noted since the first year of life; such abnormalities justify the use of melatonin for insomnia in these populations (De Leersnyder, 2006; Tordjman et al, 2013). The use of melatonin for treating chronic sleep–wake cycle disorders of children with ASD/NGD is increasing (Rossignol and Frye, 2011; Cortesi et al, 2012; Gringras et al, 2012; 2017; Malow et al, 2012; Cuomo et al, 2017). In a recent meta‐synthesis of published studies on the effectiveness of sleep‐based interventions for children with ASD, it was concluded that melatonin, behavioural interventions and parent education/interventions appear the most effective at ameliorating multiple domains of sleep problems (Cuomo et al, 2017).…”
Section: Melatonin In the Treatment Of Circadian Rhythm And Sleep Dismentioning
confidence: 99%
“…A growing body of evidence indicates abnormal melatonin secretion and circadian rhythmicity in children with neurodevelopmental disorders, specifically ASD, which may explain the abnormal development of sleep/wake cycles, noted since the first year of life; such abnormalities justify the use of melatonin for insomnia in these populations (De Leersnyder, 2006; Tordjman et al, 2013). The use of melatonin for treating chronic sleep–wake cycle disorders of children with ASD/NGD is increasing (Rossignol and Frye, 2011; Cortesi et al, 2012; Gringras et al, 2012; 2017; Malow et al, 2012; Cuomo et al, 2017). In a recent meta‐synthesis of published studies on the effectiveness of sleep‐based interventions for children with ASD, it was concluded that melatonin, behavioural interventions and parent education/interventions appear the most effective at ameliorating multiple domains of sleep problems (Cuomo et al, 2017).…”
Section: Melatonin In the Treatment Of Circadian Rhythm And Sleep Dismentioning
confidence: 99%
“…Other medications used in this age group are benzodiazepines such as clonazepam that is available in a sublingual form. Melatonin is also often tried by parents and clinicians in this age group [3][4][5][6]. Some clinicians, in particular child psychiatrists, will recommend clonidine, an alpha 2 receptor agonist, in this population.…”
Section: Age-related Manifestations Of Insomniamentioning
confidence: 99%
“…There are tudies [17,18] that show a prevalence of between 40 and 86% of sleep problems in children with ASD, including conciliation problems, maintenance and decreased of total sleep duration. These problems also correlate with changes in mood, gastrointestinal problems, and greater difficulties in social interaction of these children, as well as an increase of stereotypies and communication problems [9].…”
Section: Use Of Melatonin In Children With Autism Spectrum Disordermentioning
confidence: 99%
“…The sample consisted of 24 children between 3 and 10 years with ASD [18]. They all showed an increase in sleep latency more than 30 minutes.…”
Section: Use Of Melatonin In Children With Autism Spectrum Disordermentioning
confidence: 99%